Rancang Bangun Sistem Informasi Pelayanan Publik pada Kecamatan Lais dengan Metode Agile - Ririn Silviana; Rezki Syaputra; Padel Mohammad Agam (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Government institutions are increasingly compelled to optimize public services through integrated digital systems in response to rapid advancements in information technology. The Lais District Office continues to face operational challenges, including manual service submissions, delays in verification processes, and limited access to service status information. This study aims to design and develop a web-based public service information system to advance efficiency, transparency, and accessibility. The Agile method with an iterative approach was employed, encompassing planning, design, development, testing, and evaluation stages. Data were collected through observation, interviews, and literature review to identify system requirements. The system provides features including online service submission, multi-level verification, real-time status tracking, and digital document management. Functional testing confirmed that all primary features operate correctly without critical errors. The evaluation involved 30 internal staff members, and reliability testing demonstrated adequate consistency (Cronbach's Alpha > 0.7). Statistical analysis further reveals that system quality exerts a significant effect on user satisfaction (p < 0.05), with a coefficient of determination (R²) of 0.521, indicating that the developed system successfully establishes a structured digital workflow and strengthens transparency in service status monitoring.